Gnaphosa serzonshteini, a replacement name for Gnaphosa zonsteini Fomichev & Marusik, 2017 (Araneae: Gnaphosidae) - Fomichev, Alexander A.; Marusik, Yuri M. (Zootaxa, 2017)
Gnaphosa zonsteini Fomichev & Marusik, 2017, belonging to the rasnitsyni-group, was recently described from western Mongolia based on both sexes (Fomichev & Marusik 2017). This species was named in honour of our colleague and friend Sergei L. Zonstein (Tel Aviv, Israel) on occasion of his 60th birthday. While describing it, we overlooked that this species name already existed: Gnaphosa zonsteini Ovtsharenko, Platnick & Song, 1992. That species belongs to the muscorum-group, its description was based on several females collected in Kyrgyzstan (Ovtsharenko et al. 1992), which is the only country from where it is recorded so far (Mikhailov 2013). It was also named after Sergei Zonstein, who collected the holotype. Both species are known from a single taxonomic entry (World Spider Catalog 2017).